The relationship between maternal and infant empathy: The mediating role of responsive parenting - Liu, Hang; Zhu, Yuning; Cai, Xiaoqi; Ma, Zhengmei; Wang, Lu (Frontiers in Psychology, 2022)
Individual empathy emerges during infancy, and its development is influenced by family environmental factors such as parental characteristics and parenting style. In this study, we examined how maternal empathy was related to infant empathy and the mediating role of responsive parenting in this relationship using situational observation and scale measurement data. Thirty-three infants aged 11–30 months (M = 20.18, SD = 5.18) and their mothers (all from middle-income Chinese families) participated in simulated distress scenarios and structured mother–infant interaction sessions. These paradigms are widely used to study infant empathy and responsive parenting. The maternal empathy levels were measured using the Adult Empathy Scale (E-scale). The results indicate that (1) by their second year, infants largely acquire the capacity for other-oriented empathy and display significantly greater levels of empathy toward their mothers than toward strangers; (2) maternal empathy is significantly and positively correlated with responsive parenting and infant empathy, responsive parenting is significantly and positively correlated with infant empathy; and (3) responsive parenting fully mediates the effect of maternal empathy on infant empathy. These findings indicate that maternal empathy level can be enhanced to improve the quality of parent–child interaction, thereby promoting infant empathy development.